Weight Training Effect of Multi-Poundage System on Bench Press Ability - Nolfie Piri; Ellen Bernadeth Lomboan; Fredrik Alfrets Makadada (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2019)
This study discusses about find out how weight training effect of multi-poundage system on bench press ability in students majoring in coaching education. The research design used in this study refers to the experimental design using "Randomized Control groups pre test and post test desing. This research was conducted at the UNIMA Tondano sports hall. When the study was conducted from June 2019 for eight weeks with a frequency of three meetings per week. The population used in the study were 20 students who were randomly drawn students from the Department of Education FIK UNIMA, which were then divided into groups of 10 students each. The result shows that the research hypothesis which states that: the average bench press ability of the experimental group who were given training for eight weeks was 2.10% higher than the control group who were not given training. This is proven true by rejecting H0 because t arithmetic is greater than t table and accepting the statistical hypothesis which means the average ability of the experimental group's bench press is better than the control group's bench press ability